Suggestions for Alternative Measures of Budget Balance for South Africa - Jacobs, Davina (IMF Working Papers; Working Paper, 2002)
The following hypothesis was set and tested by this study: is the conventional budget balance, as generally accepted and used, still relevant for South Africa? The paper found that several possible alternatives are available but each must be viewed from the standpoint of their applicability to the South African context. Several were not suitable for South Africa-only because of a serious lack of available data needed to make them operational. The paper also highlights the need for reforms in government financial information in South Africa.